2022
DOI: 10.1002/advs.202104708
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐Response Oxygen Optical Fiber Sensor based on PEA2SnI4 Perovskite with Extremely Low Limit of Detection

Abstract: Oxygen sensor is an important technique in various applications including industrial process control, medical equipment, biological fabrication, etc. The reported optical fiber‐based configurations so far, using gas‐sensitive coating do not meet the stringent performance targets, such as fast response time and low limit of detection (LOD). Tin‐based halide perovskites are sensitive to oxygen with potential use for sensor applications. Here, the halide perovskite‐based oxygen optical fiber sensor by combining p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Our previous work has investigated the oxygen-induced luminescence quenching effects of PEA 2 SnI 4 films and demonstrated their potential use in optical oxygen sensors. , In this work, we first report a mixed-phase PEA 6 SnI 8 single crystal with a triclinic phase in the surface and a hexagonal phase in the interior, it can also be called a PEA 6 SnI 8 perovskite derivative. , The mixed-phase PEA 6 SnI 8 single crystal was found to exhibit ultrahigh fluorescent humidity sensitivity with a detection limit of 0.02 ppm to detect trace water in dried gases. Moreover, the sensitive spectral variation and reversible structural transformation enable a quantitative humidity analysis and reproducibility of the mixed-phase PEA 6 SnI 8 single crystal.…”
mentioning
confidence: 93%
“…Our previous work has investigated the oxygen-induced luminescence quenching effects of PEA 2 SnI 4 films and demonstrated their potential use in optical oxygen sensors. , In this work, we first report a mixed-phase PEA 6 SnI 8 single crystal with a triclinic phase in the surface and a hexagonal phase in the interior, it can also be called a PEA 6 SnI 8 perovskite derivative. , The mixed-phase PEA 6 SnI 8 single crystal was found to exhibit ultrahigh fluorescent humidity sensitivity with a detection limit of 0.02 ppm to detect trace water in dried gases. Moreover, the sensitive spectral variation and reversible structural transformation enable a quantitative humidity analysis and reproducibility of the mixed-phase PEA 6 SnI 8 single crystal.…”
mentioning
confidence: 93%
“…Various types of NH 3 sensors have been reported during the last decades [ 5 , 6 , 7 ]. Among them, due to the merits of small size, resistance to electromagnetic interference, and high sensitivity [ 8 ], optical fiber sensors have been widely studied in the field of gas sensing [ 9 , 10 , 11 , 12 ]. For instance, Xu et al [ 13 ] reported a highly sensitive NH 3 sensor by coating graphene oxide (GO)/cellulose acetate (CA) on the surface of a long-period fiber grating (LPFG).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In T h i s c o n t e n t i s addition, the structure of perovskites is highly sensitive to various physical and chemical stimuli, such as temperature, humidity, light, oxygen, organic gas/vapor, etc, because of the weak bonding energy of the ionic metal halide network. 14 Therefore, the impressible crystal structure endows perovskites with PL switching behaviors, including thermochromism, hydrochromism, photochromism, vapochromism, mechanochromism, and so on. 15 As a consequence, perovskite materials can be utilized as fluorescent sensors toward external stimuli by means of turn-off PL switching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, three-dimensional (3D) halide perovskites of CsPbX 3 have been considered as burgeoning luminescent materials with several advantages of a simple preparation method, wide and finely tunable emission wavelength range, narrow linewidth, and high photoluminescence quantum yield (PLQY). , Until now, luminescent perovskite nanocrystals have attracted extensive attention all over the world, with wide applications in advanced optoelectronic display devices, lighting-emitting diodes, lasers, X-ray scintillation, etc. , In addition, the structure of perovskites is highly sensitive to various physical and chemical stimuli, such as temperature, humidity, light, oxygen, organic gas/vapor, etc, because of the weak bonding energy of the ionic metal halide network . Therefore, the impressible crystal structure endows perovskites with PL switching behaviors, including thermochromism, hydrochromism, photochromism, vapochromism, mechanochromism, and so on .…”
Section: Introductionmentioning
confidence: 99%